Bulletin 71 Fullers Earth - Charles L. Parsons (The National Institute for Occupational Safety and Health (NIOSH), 1913)
The United States produces all of the fuller's earth used for re- fining petroleum within its borders. On the other hand, most of the fuller's earth used in bleaching edible oils has been imported from England. Recently a few of the refiners of cottonseed oil have begun to utilize domestic fuller's earth, whereas others have been unable to substitute it successfully for English earth in their practice. Many samples of American earth distinctly superior in bleaching power to the English earth have come to the attention of the Bureau of Mines. For these reasons an investigation of the mining, preparation, and use of fuller's earth in this country, especially in its application to edible oils, was conducted in order to ascertain why our own raw material has been deemed inapplicable to our needs. During the calendar year 1912, according to figures of the United States Geological Survey," there were imported into the United States 1,970 tons of unground fuller's earth, valued at $11,619, and 17,139 tons of ground fuller's earth, valued at $133,718, these values being based on the wholesale market price at the port of origin. The addition of transportation charges, commissions, etc., make the price to the American refiner $14.50 to $16 per ton. Accord- ing to the latest figures compiled by the United States Geological Survey, the United States in 1912 produced 32,715 tons of fuller's earth, valued at $305,522, or $9.34 per ton, at the mine. Most of this domestic production was from three plants in Florida and one in southwestern Georgia and was used almost wholly for decolorizing petroleum. A small amount from other localities was used in the refining of edible oils. No figures definitely differentiating fuller's earth from other clays are kept in regard to our exports, but it is certain that several thousand tons of domestic earth was exported to Germany, and it is also true that German refiners of edible oils have